“The Task of the Translator”: Walter Benjamin’s Essay in English, a Forschungsbericht - Ingram, Susan (TTR)

(untitled) (Association canadienne de traductologie, 1997)
Abstract"The Task of the Translator" : Walter Benjamin's Essay in English, a Forschungsbericht — This overview of the English-language reception of Benjamin's "Die Aufgabe des Übersetzers" charts the fate of the essay in English from its 1968 inception, through the hermeneutic and polysystemic turns in translation studies, to the influence of deconstruction and translation on English-language scholarship.